Social Glue and Post-COVID Labour Markets: Evidence from a Task Census of a Large Corporation - Kennedy, Mark T.; Molina-Solana, Miguel (2020)
ABSTRACT This research analyses the text of the complete set of job descriptions for a large corporation to produce a census of tasks useful for modelling likely technology-enabled changes to work. After briefly explaining the method for producing the task census, we describe a theme of tasks that appear widely in jobs not only across units, but also up and down the hierarchy. To summarize this finding, we call it social glue because the recurring tasks tend social ties that facilitate information exchange essential to performance of both individual jobs and the organization overall. In discussion of what social glue means for the future of work in a post-COVID world, we suggest the current rapid adoption of video-calling technologies and collaboration tools has already laid a foundation for new approaches to social glue that will have profound and lasting implications for job design, organization structure, and commuting patterns. ABOUT THE AUTHOR/S Mark T. Kennedy Imperial College London mark.kennedy@imperial.ac.uk Dr. Kennedy's research focuses on the emergence of new markets and industries and the more basic building blocks of organising—categories, identities, forms, strategies, practices, reputation criteria and so on. Within this broad topic, he pays particular attention to meaning construction processes, often by using text-mining techniques to extract and analyze patterns of association among actors, ideas and objects as they appear in conventional and new social media. His publications have appeared in American Sociological Review, Academy of Management Journal, Organization Science, Journal of Managment Studies, and Research in the Sociology of Organizations. https://www.imperial.ac.uk/people/mark.kennedy Miguel Molina-Solana Imperial College London m.molina-solana@imperial.ac.uk Dr Miguel Molina-Solana currently holds a Marie Curie Research Fellowship position at the University of Granada. Before, he was a Marie Curie Research Fellow at Imperial's Data Science Institute (DSI). He maintains a close collaboration with the College by participating in research projects, supervising students and performing short visits. His research experience comprises applied work in the areas of Knowledge Representation, Data Understanding, and AI. https://www.imperial.ac.uk/people/m.molina-solana New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).